Inovação Gerencial e Práticas de Gestão de Pessoas voltadas à Inovação como antecedentes de Perfis de Comprometimento Organizacional - Montenegro, Adauto de Vasconcelos (2020)
Considering the studies in the field of Organizational Commitment, this thesis has as theoretical basis the studies on this construct, together with the Organizational Commitment Profiles, Personnel Management Practices focused on Innovation and Managerial Innovation. This study aimed to analyze how Managerial Innovation and Personnel Management Practices focused on Innovation promote certain Organizational Commitment Profiles of technician servants, managers, and outsourced staff. This is an explanatory reasearch with an ex post facto correlational delineation. It used a sample of 470 workers, among public technician servants, managers, and outsourced staff of two Brazilian Northeastern federal universities. Data collection was carried out by means of three instruments, regarding the differentiated aspects of the three occupational categories, and it included sociodemographic questionnaire and ranges for the investigation of Organizational Commitment (components of affection, normative, and continuance), Managerial Innovation, and Personnel Management Practices focused on Innovation (Delegation, Recruitment and Retention, Incentives, Training and Communication). The data were analyzed by means of Statistical Package for the Social Sciences (SPSS), MPlus and Iramuteq, in which the following analyses were carried out: latent profiles analysis, regression analysis, variance analysis, exploratory factorial analysis, and similarity analysis. We evaluated the factorial structure of the utilized ranges, which pointed to the trifactorial structure of the Organizational Commitment with its three components: Affection, Normative, and Continuance; concerning the Personnel Management Practices focused on Innovation, the resulting factorial structure pointed to four practices only: Delegation, Recruitment and Retention, Tangible and Intangible Incentives, and Training. With respect to the main results, four Organizational Commitment Profiles were identified: Non-Committed, Affective-Continuance Committed, Moderate, and Affective Committed. In terms of the perception to Managerial Innovation and Personnel Management Practices focused on Innovation, it was highlighted that the Non-Committed were the ones who noticed the least both the process of Managerial Innovation and all the Personnel Management Practices focused on Innovation, whereas those who noticed them the most were the Affective-Continuance Committed. Concerning the predictive power of such constructs, it was highlighted that only the practices of Delegation and Recruitment and Retention acted in a significant way for the following Commitment Profiles: Delegation predicted positively the profiles of the Affective-Continuance Committed and the Moderate, whereas Recruitment and Retention predicted positively the Moderate Profile. Both Delegation and Recruitment and Retention predicted negatively the Non-Committed Profile. These results confirmed partially the hypotheses of the research and those constitute as an importante contribution for the Brazilian research regarding commitment, once it was investigated according to the field of Managerial Innovation and Personnel Management Practices focused on Innovation, by utilizing the approach of Commitment Profiles and promoting such anlyses into three different occupational categories.